Answer:
Equation in slope-intercept form is ![\mathbf{y=3x}](https://tex.z-dn.net/?f=%5Cmathbf%7By%3D3x%7D)
Step-by-step explanation:
We need to write equation in slope-intercept form to represent the relationship shown in the table.
The general equation of slope-intercept form is: ![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
where m is slope and b is y-intercept.
Finding slope using point (-2,-6) and (0,0)
The formula used is: ![Slope=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=Slope%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
We have ![x_1=-2, y_1=-6, x_2=0, y_2=0](https://tex.z-dn.net/?f=x_1%3D-2%2C%20y_1%3D-6%2C%20x_2%3D0%2C%20y_2%3D0)
Putting values and finding slope
![Slope=\frac{y_2-y_1}{x_2-x_1}\\Slope=\frac{0-(-6)}{0-(-2)}\\Slope=\frac{6}{2}\\Slope=3](https://tex.z-dn.net/?f=Slope%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%5C%5CSlope%3D%5Cfrac%7B0-%28-6%29%7D%7B0-%28-2%29%7D%5C%5CSlope%3D%5Cfrac%7B6%7D%7B2%7D%5C%5CSlope%3D3)
Using slope m= 3 and point (-2,-6) we can find y-intercept
![y=mx+b\\-6=3(-2)+b\\-6=-6+b\\b=-6+6\\b=0](https://tex.z-dn.net/?f=y%3Dmx%2Bb%5C%5C-6%3D3%28-2%29%2Bb%5C%5C-6%3D-6%2Bb%5C%5Cb%3D-6%2B6%5C%5Cb%3D0)
So, we have y-intercept b =0
Equation in slope-intercept form having slope m= 3 and y-intercept b =0 is:
![y=mx+b\\y=3x+0\\y=3x](https://tex.z-dn.net/?f=y%3Dmx%2Bb%5C%5Cy%3D3x%2B0%5C%5Cy%3D3x)
So, Equation in slope-intercept form is ![\mathbf{y=3x}](https://tex.z-dn.net/?f=%5Cmathbf%7By%3D3x%7D)